Corporate Alumni – What and why? - Vieira , Diana Aguiar; Reis , Camila (Conferência - Investigação e Intervenção em Recursos Humanos, 2023)
Alumni are commonly understood as the group of former students of an Educational Institution. Despite its origin in the educational context, organizations have been recognizing the value of this perspective as applied to their former employees. Some large companies already have programs to connect with ex-employees, but it is still a very new practice. What is more common are groups created by ex-employees to maintain relationships, not groups created by the company. The company's concept is to make strategic use of this network to convert it into results for the business. The company may create a network of former employees to achieve a gap in People Management or some potential outcome in the future. Reducing recruitment costs and increasing recruitment by referral are some of the outcomes pursued by companies. The Human Resources area has been increasingly demanded to provide solutions for identifying talent in the market. According to the search area, the sources of talent in the open market may be scarce. Seeking talent from competitors, universities, and the social network, among other well-known formats, can generate high costs and high time involved. The innovation in searching the network of former employees can be low cost and low time involved if the company has a structured program. Overall, Corporate Alumni programs aim to build a community focused on maintaining lasting relationships with former employees, but it can be more than that. The exponential growth of Boomerang employees—previous employees who return to an organization after the formal employment relationship has ended— is one of the factors that highlight the unique importance of the Alumni perspective in contemporaneous organizations. It is evident in research that the return of talent can be very productive because former employees already know the organizational dynamics, and have a shorter time of integration and delivery of performance, in addition to the fact that when returning employees usually show greater loyalty to the employer what, in turn, contributes to retention. The present work aims to present the general elements that constitute a corporate alumni program – “the what”. Additionally, it intends to approach the benefits of adapting educational Alumni practices into corporate organizations – “the why”. Moreover, we will present an empirical study that evaluated human resources managers’ knowledge, experience and general perceptions of Corporate Alumni. Data collection procedures included information on the aim of the study, and assurance of confidentiality was guaranteed. Participation was voluntary, and informed consent was actively provided. The introduction of the questionnaire included the following information: 'Alumni' means the group of former students of a higher education institution. 'Corporate Alumni' is an expression that means the use of the same dynamics of higher education institutions with their former students, but with the former employees of the Organizations. The online survey also included closed and open questions followed by sociodemographic questions. Data were analyzed with IBM SPSS Statistics v. 26. The sample comprises 26 Human Resources professionals (69% female). The age varies from 35 to 71 years old (mean= 49 ±9). The majority of participants work in Brazil (58%) followed by the United States (19%), Portugal (8%) and other individual countries (15%). Findings show that 46% have never heard about corporate alumni, and only 8% have participated in a corporate alumni program. Overall the participants agree on the importance of companies keeping in contact with former employees (77%), and 70% would accept to join an alumni program if invited. The majority of the participants (92%) know someone in their company who has returned to work in it, and 31% did it themselves. Potential benefits of implementing alumni projects in companies were identified by 92% of participants. Among other factors, talent acquisition and employer branding were mentioned as possible benefits. When asked to anticipate possible barriers to implementing corporate alumni programs in the companies where they work, lack of time and people to develop the alumni program and the absence of specific knowledge in the alumni area were mentioned, among other potential obstacles. Finally, suggestions for future research and practices in corporate Human Resources actions will be discussed.